ANALISA FAKTOR WILLINGNESS TO PAY PRODUK MAKANAN ORGANIK DI DENPASAR - Hendrawan, Alvin Alviandi; Sudyasjayanti, Christina (Parsimonia - Jurnal Ekonomi dan Bisnis, 2024)
The Covid-19 pandemic has changed people's lifestyles to pay more attention to their health. One of the factors that affect health is food, healthy food consists of various types, one of which is organic food which has a good projected market growth in Indonesia until 2026 of 6%. This research was conducted to determine the factors that influence the willingness to pay for organic food products in Denpasar. The number of respondents in this study was 210 respondents using purposive sampling method. The criteria for respondents in this study are those who live in Denpasar and have purchased organic food products at least once. This research is a quantitative study with a confirmatory factor analysis method using SMART PLS 3.0. Based on the findings of this study, the factors that influence the willingness to pay for organic food products are consumer knowledge, social media marketing, price fairness, perceived value and customer satisfaction.